Biodigestão anaeróbia de cama de frango em co-digestão com caldo de cana-de-açúcar - Sagula, Alex Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
A avicultura brasileira alcançou nos últimos anos níveis de produtividade e ajuste na organização e coordenação que a colocam como uma das mais competitivas do mundo. A cama de frango gerada no processo produtivo das aves demonstra ter grande potencial para a obtenção de energia com o uso de biodigestores. Objetivou-se com a execução deste trabalho avaliar a inclusão de 5 e 7% do caldo de cana de açúcar, no processo de biodigestão anaeróbia da cama de frango com separação de sólidos em sistemas contínuos de abastecimento. O experimento foi dividido em duas fases, sendo que na primeira foi realizado o preparo do inóculo com dejeto de bovino leiteiro e na segunda fase foram abastecidos oito biodigestores contínuos com o inóculo obtido + cama de frango com separação de sólidos (CFCSS), associada ao caldo de cana em diferentes proporções composto por dois tratamentos com quatro repetições. O tratamento T1 – CFCSS (Controle) e tratamento T2 – CFCSS + caldo de cana (5% por um período de 30 dias e 7 % por mais 30 dias). Foram analisados os teores de sólidos totais (ST) e sólidos voláteis (SV), potencial de hidrogênio (pH) e concentrações de micro e macronutrientes. Para os tratamentos...

The Brazilian aviculture productionin in recent years achieved levels of productivity and adjustthe organization and coordination that pose as one of the most competitive in the world.The poultry litter generated in the production process of the birds shows a high potential to produce energy using biodigesters. Objective was to evaluate the inclusion of 5 and 7% of the juice of sugar cane in the process of anaerobic digestion of poultry litter with separation of solids in a continuous system of supply. The experiment was divided into two phases with the first was conducted in the preparation of the inoculums with dairy cattle manure and the second phase were supplied with eight digesters continuous inoculums obtained + poutry litter with separation of solids (PLSS) associated cane juice in different proportions composed of 4 two treatments with four replications. The T1 – PLSS (Control) and T2 PLSS + cane juice (5% for a period of 30 days and 7% for 30 days). We analyzed the levels of total solids (TS) and volatile solids (VS), potential hydrogen (pH) and concentrations of macronutrients and micronutrients. For those treatments evaluated showed that there was a reduction of TS and VS, 66,05 and 74,33% respectively for a control 1. Treatment with 5% sugar cane juice showed a value of 0,5500 m3 of biogas and received sugar cane juice to 7% showed a value of 0,6919 m3 of biogas within 30 days of operation. These results demonstrate that the juice was effective for the methanogenic bacteriadegrade organic mattere expressing great potential for biogas production
Keywords: Biodigestor; Cana-de-açúcar; Cama de frango; Biodigestor; Poultry litter